Efficient synthesis method of polyaminopropyl phenyl silsesquioxane

By using APS and PTES in the silsesquioxane synthesis process for hydrolysis and copolycondensation, combining alkaline resin catalysts and anhydrous ethanol solvents, the existing silsesquioxane synthesis process is solved, and the problems of complex and low yields are achieved. It has an efficient and simplified silsesquioxane synthesis process, suitable for industrial production.

CN119505242APending Publication Date: 2025-02-25上海普信高分子材料有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510081015.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing silsesquioxane synthesis process is complex, difficult to control, long reaction time, low yield, and is not suitable for industrial production.

Method used

The new polysilsesquioxane with phenyl and aminopropyl structures were prepared by hydrolysis and co-polycondensation under different conditions. . This method simplifies the process flow and improves the reaction efficiency by using an alkaline resin catalyst and anhydrous ethanol as solvents.

Benefits of technology

It effectively shortens the synthesis time of silsesquioxane, improves yield, simplifies the process flow, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505242A_ABST
    Figure CN119505242A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient synthesis method of polyaminopropyl phenyl silsesquioxane, and relates to the technical field of functional silsesquioxane synthesis. According to the method, aminopropyltriethoxysilane and phenyltriethoxysilane which are simple in raw material source are subjected to hydrolysis copolycondensation under various conditions to prepare the novel polysilsesquioxane PAPSQ which simultaneously contains phenyl and aminopropyl in composition, is branched-chain or highly crosslinked in structure and is resin or granular in form. Amino functional groups are introduced into a polyphenyl silsesquioxane system by adopting a hydrolytic copolycondensation method, and the method and the route are relatively simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional silsesquioxane synthesis, in particular to a high-efficiency synthesis method of polyaminopropylphenyl silsesquioxane. Background Art

[0002] Non-functional (cyclic ladder polyphenyl silsesquioxane) PPSQ has good heat resistance and oxidation resistance, but poor reactivity, compatibility and adhesion with the substrate. Functional polyaminopropyl silsesquioxane (PASQ) has reactivity and interfacial activity, but poor storage stability and poor heat resistance. Combining the advantages of these two types of substances, it can be seen that polysilsesquioxane containing both phenyl and aminopropyl groups will have both thermal stability and reactivity. The hydrolysis and co-condensation reaction of phenylsilane monomers and aminopropylsilane monomers can combine their structural units into the same polysiloxane main chain to obtain copolymers with the advantages of both, and copolymers with various properties can be obtained by changing the ratio of the monomers.

[0003] In recent years, there have been many studies on the crystal structure of polyaminopropylsilsesquioxane ammonium salt, hexahedral cage-shaped polysilsesquioxane used as a reinforcing and toughening modifier, and reaction intermediates, but there are few studies on aminopropylsilsesquioxane phenylsilsesquioxane copolymer (PAPSQ). Tunney's patent reported the hydrolysis and co-condensation of APS and PTES in a tetra-aqueous solution, but there was no research on its structure, composition, and properties. Since the product structure is related to the reaction conditions and methods, the structure, composition, properties, and morphology of the copolymers obtained by co-condensation in different solvents, different chemical agents, and different methods are very different.

[0004] At present, the raw materials for synthesizing silsesquioxane are usually trichlorosilane containing different functional groups. However, the hydrolysis and condensation reaction of trichlorosilane is fierce and complicated, and the process conditions are difficult to control. It requires acid removal and solvent recovery, and the acidity changes during the reaction. In addition, the synthesis time of functional silsesquioxane is too long and the yield is low, which is not conducive to industrialization. Summary of the invention

[0005] In view of the above background technology, the present method uses aminopropyltriethoxysilane (APS) and phenyltriethoxysilane (PTES) with simple raw material sources to hydrolyze and co-condense under various conditions to prepare a novel polysilsesquioxane PAPSQ containing both phenyl and aminopropyl groups in composition, with a branched or highly cross-linked structure and a resin or granular form. The amino functional group is introduced into the polyphenylsilsesquioxane system by the hydrolysis and co-condensation method, and the method and route are relatively simple.

[0006] The technical solution is as follows: An efficient synthesis method of polyaminopropylphenylsilsesquioxane comprises the following steps: (1) Add 50-100 parts of ethanol, 0.5-2 parts of alkaline resin catalyst and 20-30 parts of deionized water into a three-necked flask by mass and maintain a fixed temperature; (2) using a constant pressure dropping funnel to dropwise add a solution of aminopropyltriethoxysilane and phenyltriethoxysilane into a three-necked flask; (3) After the addition is completed, continue to stir the reaction; (4) After the timing is over, the powder is washed by distillation and vacuum filtration with H2O / EtOH, and then washed with anhydrous ethanol. The washed powder is thoroughly dried under vacuum at room temperature for 16-24 hours; the fixed temperature in step (1) is set to 35-45°C.

[0007] The preparation method of the alkaline resin catalyst in step (1): The following are calculated by mass: 1) Add 100-140 parts of D201 ion exchange resin (the factory form is quaternary ammonium salt type), 1000-1500 parts of acryloyl chloride, and 3-8 parts of zinc chloride into the stirring tank 1, and stir and react at 30-40°C for 30 to 60 minutes; filter, wash with water, and dry to obtain D201 ion exchange resin containing acryloyl; 2) Add 12-24 parts of boron trifluoride ethylamine complex (CAS No.: 75-23-0), 2.4-5.5 parts of N-(3-aminopropyl)diethanolamine, 2-5 parts of triethylamine, 200-340 parts of D201 ion exchange resin containing propylene group; 1000-1200 parts of dichloroethane into stirring tank 2, filter, wash with water, and dry to obtain boron-doped D201 ion exchange resin, quaternary ammonium salt type; 3) The boron-doped D201 ion exchange resin, quaternary ammonium salt type, is then loaded into an ion exchange column for transformation to obtain a hydroxyl-type boron-doped D201 ion exchange resin, i.e., an alkaline resin catalyst.

[0008] In the transformation steps: The resin volume accounts for 20-30% of the volume of the ion exchange column; NaOH concentration: 4-10wt%; contact time: 30-60 minutes; forward wash flow rate: 15-25m / h.

[0009] In the step (2), the mass ratio of aminopropyltriethoxysilane to phenyltriethoxysilane is 1-5:5-9.

[0010] The dropping time in step (2) is 30-60 minutes.

[0011] The reaction time in step (3) is 8-13 hours.

[0012] In step (4), H 2 O / EtOH volume ratio 1:3.

[0013] Catalyst synthesis mechanism: After the allyl D201 ion exchange resin undergoes an aminoolefin addition reaction with a boron trifluoride ethylamine complex and N-(3-aminopropyl)diethanolamine, the boron trifluoride complex is grafted and loaded, and then transformed into an -OH type, finally obtaining a modified D201 ion exchange resin.

[0014] The introduction of boron trifluoride ethylamine complex and N-(3-aminopropyl)diethanolamine increases the active sites on the resin surface, which react with specific groups on the propyl D201 ion exchange resin through aminoolefin addition reaction to form stable chemical bonds. The formation of this chemical bond strengthens the interaction between the resin and the reactants, thereby improving the catalytic efficiency.

[0015] The technical effects of using boron trifluoride complex and diethanolamine to improve the hydrolysis polymerization conversion rate of aminopropyltriethoxysilane and phenyltriethoxysilane include the following aspects: 1. Enhanced catalytic activity: Boron trifluoride complex, as a strong Lewis acid, can effectively catalyze the hydrolysis and condensation reactions of silane. Its complex with diethanolamine further enhances the catalytic activity, because diethanolamine not only provides additional electron density, but also may form hydrogen bonds with silane through its hydroxyl group, thereby promoting the hydrolysis reaction.

[0016] 2. Improved stability: The complex formed by the boron trifluoride complex and diethanolamine has high stability under the reaction conditions and is not easy to decompose or deactivate. This means that during the catalytic process, the active center can continue to play a role, thereby improving the overall catalytic efficiency and product yield.

[0017] 3. Optimization of reaction conditions: Using boron trifluoride complex and diethanolamine as catalysts, efficient hydrolysis and condensation reactions can be achieved under relatively mild conditions. This helps to reduce the occurrence of side reactions and improve the purity and selectivity of the product.

[0018] Technical effects: Compared with existing technologies, this method for synthesizing PAPSQ has the following advantages: The raw materials APS and PTES selected in this scheme are cheaper, and the solvent is anhydrous ethanol, because the byproduct of ethoxysilane hydrolysis is also ethanol, so as to ensure that the component system in the system is simpler, so as to facilitate subsequent separation and purification. In addition, the ratio of APS and PTES is adjusted to achieve the highest yield ratio; at the same time, this method effectively reduces the reaction time and improves economic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Shown is the reaction mechanism of the present invention. DETAILED DESCRIPTION

[0020] The features of the present invention are further illustrated by the following examples, but the protection scope of the present invention is not limited by the examples.

[0021] Catalyst Preparation Example 1 1) Add 100g D201 ion exchange resin (factory form is quaternary ammonium salt type), 1000g acryloyl chloride, 3g zinc chloride into stirring tank 1, stir and react at 30°C for 30 minutes; filter, wash with water, and dry to obtain D201 ion exchange resin containing acryloyl; 2) Add 12g of boron trifluoride ethylamine complex (CAS No.: 75-23-0), 2.4g of N-(3-aminopropyl)diethanolamine, 2g of triethylamine, 200g of D201 ion exchange resin containing propylene group, and 1000g of dichloroethane into stirring tank 2, filter, wash with water, and dry to obtain boron-doped D201 ion exchange resin, quaternary ammonium salt type; 3) The boron-doped D201 ion exchange resin, quaternary ammonium salt type, is then loaded into an ion exchange column for transformation to obtain a hydroxyl-type boron-doped D201 ion exchange resin, i.e., 1# alkaline resin catalyst.

[0022] In the transformation steps: The resin volume accounts for 20% of the ion exchange column volume; NaOH concentration: 4wt%; contact time: 30 minutes; forward wash flow rate: 15m / h.

[0023] Catalyst Preparation Example 2 1) Add 120g D201 ion exchange resin (factory form is quaternary ammonium salt type), 1250g acryloyl chloride, 5g zinc chloride into stirring tank 1, stir and react at 35°C for 45 minutes; filter, wash with water, and dry to obtain D201 ion exchange resin containing acryloyl; 2) Add 18g of boron trifluoride ethylamine complex (CAS No.: 75-23-0), 4.8g of N-(3-aminopropyl)diethanolamine, 3.5g of triethylamine, 280g of D201 ion exchange resin containing propylene group, and 1100g of dichloroethane into stirring tank 2, filter, wash with water, and dry to obtain boron-doped D201 ion exchange resin, quaternary ammonium salt type; 3) The boron-doped D201 ion exchange resin, quaternary ammonium salt type, is then loaded into an ion exchange column for transformation to obtain a hydroxyl-type boron-doped D201 ion exchange resin, i.e., 2# alkaline resin catalyst.

[0024] In the transformation steps: The resin volume accounts for 25% of the volume of the ion exchange column; NaOH concentration: 7wt%; contact time: 45 minutes; forward wash flow rate: 20m / h.

[0025] Catalyst Preparation Example 3 1) Add 140g D201 ion exchange resin (factory form is quaternary ammonium salt type), 1500g acryloyl chloride, 8g zinc chloride into stirring tank 1, stir and react at 40°C for 60 minutes; filter, wash with water, and dry to obtain D201 ion exchange resin containing acryloyl; 2) Add 24g of boron trifluoride ethylamine complex (CAS No.: 75-23-0), 5.5g of N-(3-aminopropyl)diethanolamine, 5g of triethylamine, 340g of D201 ion exchange resin containing propylene group, and 1200g of dichloroethane into stirring tank 2, filter, wash with water, and dry to obtain boron-doped D201 ion exchange resin, quaternary ammonium salt type; 3) The boron-doped D201 ion exchange resin, quaternary ammonium salt type, is then loaded into an ion exchange column for transformation to obtain a hydroxyl-type boron-doped D201 ion exchange resin, namely, 3# alkaline resin catalyst.

[0026] In the transformation steps: The resin volume accounts for 30% of the ion exchange column volume; NaOH concentration: 10wt%; contact time: 60 minutes; forward wash flow rate: 25m / h.

[0027] Example 1 (1) Add a mixed solution of APS and PTES in different proportions, 75 ml of ethanol, 1 g of 1# alkaline resin catalyst, and 25 ml of deionized water into a three-necked flask and keep the temperature at 40°C; (2) Use a constant pressure dropping funnel to add the solution composed of APS and PTES dropwise. The addition time is 60 minutes.

[0028] (3) After the addition is complete, continue stirring for 8 hours.

[0029] (4) After the timing is over, use distilled H 2 The washed powder was then vacuum filtered and washed with O / EtOH (1 / 3 by volume) and then washed with pure ethanol. The washed powder was thoroughly dried under vacuum at room temperature for 20 h.

[0030] The steps of Examples 2-8 and Comparative Examples 1-2 are basically the same as those of Example 1, except for the differences shown in Table 1: Table 1 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Comparative Example 1 Comparative Example 2 Component 1 APS:PTES1:9 APS:PTES1:4 APS:PTES3:7 APS:PTES2:3 APS:PTES1:1 APS:PTES1:9 APS:PTES1:9 APS:PTES1:9 APS PTES Component 2 Ethanol 75ml Ethanol 75ml Ethanol 75ml Ethanol 75ml Ethanol 75ml Ethanol 75ml Ethanol 75ml Ethanol 75ml Ethanol 75ml Ethanol 75ml Component 3 1# basic resin catalyst 1g 2# basic resin catalyst 1g 2# basic resin catalyst 1g 3# basic resin catalyst 1g 3# basic resin catalyst 1g 1# basic resin catalyst 1g 1# basic resin catalyst 1g 1# basic resin catalyst 1g 1# basic resin catalyst 1g 1# basic resin catalyst 1g Component 4 Deionized water 25ml Deionized water 25ml Deionized water 25ml Deionized water 25ml Deionized water 25ml Deionized water 25ml Deionized water 25ml Deionized water 25ml Deionized water 25ml Deionized water 25ml Adding time 1h 1h 1h 1h 1h 1h 30min 1h 1h 1h Reaction time 8h 8h 8h 8h 8h 8h 8h 12h 8h 8h Reaction temperature 40℃ 40℃ 40℃ 40℃ 40℃ 30℃ 40℃ 40℃ 40℃ 40℃ Yield 81.14% 73.33% 60.01% 47.47% 26.97% 80.84% 81.57% 80.21% 0% 91.21% As can be seen from Table 1, the methods described in Examples 1 to 5 of the present invention can shorten the preparation time of PAPSQ to 8 hours, simplify the synthesis steps, and achieve a very high yield.

[0031] By comparing Example 1 with Example 6, it can be seen that the yield is not affected when the reaction temperature is low.

[0032] By comparing Example 1 with Example 7, it can be seen that the effect of the water addition time on the yield is relatively small and the controllable range is within 30 minutes.

[0033] By comparing Example 1 with Example 8, it can be seen that the reaction time of 8 hours and 12 hours has little effect on the yield, which means that 8 hours is enough for APS and PTES to hydrolyze and condense into a polymer, which greatly reduces the reaction time and is conducive to industrial production.

[0034] By comparing Examples 1 to 5 with Comparative Examples 1 to 2, it can be seen that the initial hydrolysis of APS and PTES produces silanol functional oligomers. These silicon-hydrogen functional reactions are very active and then condensed into silsesquioxanes in an alkaline catalyst. When only PTES is added as a single component, a white precipitate is obtained after the reaction is completed, with a yield of more than 90%. However, when only APS is added as a single component, no precipitate is produced after the reaction is completed, but a clear solution appears. This may be due to the reaction of the amino group with the polar ethanol-H 2 O solvent. The simultaneous hydrolysis of APS and PTES leads to co-condensation, but the product state varies with the change of APS / PTES molar ratio. When the ratio is small, a white precipitate appears, but the yield decreases with the increase of APS.

[0035] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the embodiments. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. An efficient synthesis method of polyaminopropylphenylsilsesquioxane, characterized in that: The following steps are involved: (1) Add 50-100 parts of ethanol, 0.5-2 parts of alkaline resin catalyst and 20-30 parts of deionized water into a three-necked flask by mass and maintain a fixed temperature; (2) using a constant pressure dropping funnel to dropwise add a solution of aminopropyltriethoxysilane and phenyltriethoxysilane into a three-necked flask; (3) After the addition is completed, continue to stir the reaction; (4) After the timing is completed, the powder is washed by vacuum filtration with H2O / EtOH distillation, and then washed with anhydrous ethanol. The washed powder is thoroughly dried under vacuum at room temperature for 16-24 h; The alkaline resin catalyst is prepared by reacting D201 ion exchange resin containing acryl, boron trifluoride ethylamine complex and N-(3-aminopropyl)diethanolamine and then transforming the reaction mixture.

2. The efficient synthesis method of polyaminopropylphenylsilsesquioxane according to claim 1, characterized in that: The fixed temperature in step (1) is set to 35-45°C.

3. The efficient synthesis method of polyaminopropylphenylsilsesquioxane according to claim 1, characterized in that: The preparation method of the alkaline resin catalyst in step (1): The following are calculated by mass: 1) Add 100-140 parts of D201 ion exchange resin (the factory form is quaternary ammonium salt type), 1000-1500 parts of acryloyl chloride, and 3-8 parts of zinc chloride into the stirring tank 1, and stir and react at 30-40°C for 30 to 60 minutes; filter, wash with water, and dry to obtain D201 ion exchange resin containing acryloyl; 2) Add 12-24 parts of boron trifluoride ethylamine complex, 2.4-5.5 parts of N-(3-aminopropyl)diethanolamine, 2-5 parts of triethylamine, 200-340 parts of D201 ion exchange resin containing acryl group, and 1000-1200 parts of ethylene dichloride into stirring tank 2, filter, wash with water, and dry to obtain boron-doped D201 ion exchange resin, quaternary ammonium salt type; 3) The boron-doped D201 ion exchange resin, quaternary ammonium salt type, is then loaded into an ion exchange column for transformation to obtain a hydroxyl-type boron-doped D201 ion exchange resin, i.e., an alkaline resin catalyst.

4. The efficient synthesis method of polyaminopropylphenylsilsesquioxane according to claim 3, characterized in that: In the transformation steps: The resin volume accounts for 20-30% of the volume of the ion exchange column; NaOH concentration: 4-10wt%; contact time: 30-60 minutes; forward wash flow rate: 15-25m / h.

5. The efficient synthesis method of polyaminopropylphenylsilsesquioxane according to claim 1, characterized in that: In the step (2), the mass ratio of aminopropyltriethoxysilane to phenyltriethoxysilane is 1-5:5-9.

6. The efficient synthesis method of polyaminopropylphenylsilsesquioxane according to claim 1, characterized in that: The dropping time in step (2) is 30-60 minutes.

7. The efficient synthesis method of polyaminopropylphenylsilsesquioxane according to claim 1, characterized in that: The reaction time in step (3) is 8-13 hours.

8. The efficient synthesis method of polyaminopropylphenylsilsesquioxane according to claim 1, characterized in that: In the step (4), the volume ratio of H2O / EtOH is 1:3.

Citation Information

Cited By

  • Efficient synthesis method for polyaminopropylphenylsilsesquioxane

    WO2026152555A1